Keragaman Karakter Morfo-Agronomi dan Keanekaragaman Galur- galur Cabai Besar (Capsicum annuum L.) - Agustina, Nur Indah; Waluyo, Budi (Jurnal AGRO, 2017)
The objective of this research was to study the variability of morpho-agronomic characters, genetic distance, and genetic diversity of 39 chili pepper lines. The experiment was conducted from January until June 2017, in Agro Techno Park of Universitas Brawijaya, at Jatikerto, Malang Regency. This research was conducted by using randomized block design (RBD) with treatment of 39 chili pepper genotypes repeated two times. Observation was made on agronomic characters. The variability was analyzed by principal components analysis (PCA) with the approach of the Pearson correlation. Agglomerative hierarchical clustering (AHC) with the Pearson correlation coefficient of similarity and agglomeration method unweighted pair-group average was performed for lines grouping. Genetic diversity was obtained using Shannon index (H’) and Simpson index (D). The agronomic characters variability of chili pepper lines based on principal component analysis (PCA) was divided into 9 principal components with cumulative variability value 82,59%. Genetic distance was divided into four main groups at coefficient of 91% -100%. Mantel test of genetic distance based on 24 qualitative and 18 quantitative characters showed a significant positive correlation coefficient (r = 0,173 and P <0,0001). Diversity index based Shannon index (H’) included category 1-3 showed that the level of diversity was medium, and based on Simpson index 0,39 showed a low level diversity. The percentage proportion of the abundance in four groups showed a variation. Group A had the highest abundance and group D was the lowest.